2001
DOI: 10.1097/00000658-200101000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single-Dose Prophylactic Ampicillin and Sulbactam on Wound Infection After Tension-Free Inguinal Hernia Repair With Polypropylene Mesh

Abstract: This study documented a significant (10-fold) decrease in overall wound infections when single-dose, intravenous AS was used during Lichtenstein hernia repair. Deep infections and wound infection-related readmissions were also reduced by the use of AS. Proponents of mesh repairs may therefore be advised to use prophylactic single-dose intravenous antibiotic coverage in the light of the results of this trial. AS proved to be an effective antimicrobial agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
132
5
13

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(155 citation statements)
references
References 23 publications
4
132
5
13
Order By: Relevance
“…Yerdel et al (35) claimed that the use of prophylactic single dose intravenous antibiotic would reduce the risk of wound infection.…”
Section: Antibiotherapymentioning
confidence: 99%
“…Yerdel et al (35) claimed that the use of prophylactic single dose intravenous antibiotic would reduce the risk of wound infection.…”
Section: Antibiotherapymentioning
confidence: 99%
“…All wound infection were treated with antibiotics, mesh removal was not required in any of the cases. In our study antibiotics do not seem to prevent wound infection in any case, as these differences were not stasistically significant but Turkish trial reported significantly different infection rates between group receiving a single dose of amipicillin plus sulbactam and placebo group [9]. Yerdel et al documented a significant decrease in overall wound infection rate 9% to 0.7% when single dose, intravenous amipicillin sulbactam was used during Lichtenstein hernia repair [9].…”
Section: Discussionmentioning
confidence: 47%
“…The postoperative infection rate in open inguinal hernia mesh repair has been reported as high as 9% (Yerdel et al, 2001), whereas laparoscopic ventral hernia mesh repair has a postoperative mesh infection rate of 0.7-2%, and open ventral hernia mesh repair has an infection rate as high as 7-18% (Ríos et al, 2001;Itani et al, 2010). Mesh infection is a great challenge for surgeons.…”
Section: Discussionmentioning
confidence: 99%